Clockwork prince [compact disc, unabridged] - Clare, Cassandra (Clare, Cassandra. Infernal devices, 2011)
As the Council attempts to strip Charlotte of her power, sixteen-year-old orphaned shapechanger Tessa Gray works with the London Shadowhunters to find the Magister and destroy his clockwork army, learning the secret of her own identity while investigating his past.